2018
DOI: 10.1159/000491787
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neurodevelopmental Outcome of Monochorionic Twins after Laser Therapy or Umbilical Cord Occlusion for Twin-Twin Transfusion Syndrome

Abstract: Introduction: We sought to assess the incidence of severe neurodevelopmental impairment (NDI) in monochorionic twins treated for twin-twin transfusion syndrome (TTTS) and compare it to the incidence in uncomplicated monochorionic twins. Material and Methods: We included TTTS pregnancies treated by fetoscopic selective laser coagulation (FSLC) or umbilical cord occlusion (UCO) in 2004–2015. Primary outcome was severe NDI defined as cerebral palsy, bilateral blindness or bilateral deafness (ICD-10 diagnoses), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Few studies report neonatal morbidity and mortality after SFT, and even fewer evaluate neurological or psychomotor development, reporting normal development in the age of two years in 70-92%, explaining impaired development by prematurity [15][16][17][18][19][20]. In our series, no specific neonatal morbidity was reported after both BCC and ILC, except for those that are a consequence of prematurity.…”
Section: Discussionmentioning
confidence: 48%
“…Few studies report neonatal morbidity and mortality after SFT, and even fewer evaluate neurological or psychomotor development, reporting normal development in the age of two years in 70-92%, explaining impaired development by prematurity [15][16][17][18][19][20]. In our series, no specific neonatal morbidity was reported after both BCC and ILC, except for those that are a consequence of prematurity.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, our data showed that 70 % of patients with a preoperative cervical length ≤ 15 mm had at least one surviving twin. However, since neurological outcome is strongly associated with GA at birth, high preterm delivery rate < 32 weeks in this subset of patients should also be discussed [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…31 Schou et al investigated the prevalence of severe neurodevelopment impairment (cerebral palsy, bilateral blindness and/or deafness, and severe cognitive and/or motor delay) in children at the age of 2 years after fetoscopic laser surgery for TTTS. 32 Nine out of 86 children (10.5%) were affected. It is important to know that follow-up studies reported varying rates of cerebral palsy and neurodevelopment impairment in TTTS treated cases with laser surgery.…”
Section: Selective Fetal Reductionmentioning
confidence: 99%